Orthodontic management of palatally displaced maxillary canine with bracket modification approach : a case report = Manejo ortodóntico del canino maxilar desplazado hacia palatino con énfasis en la modificación de brackets : reporte de un caso - Doan, Tri Minh
The maxillary permanent canine is known to be susceptible to displacement due to its long and complex journey from initial formation to its eventual placement in the occlusal position. This report presents a case of a 15-year-old female patient with a palatally positioned left maxillary canine. A fixed orthodontic approach using 0.022-slot brackets with MBT prescriptions was employed. During treatment, an open-coil spring and a power chain were utilized to reposition the canine within the dental arch. Additionally, a bracket originally designed for the upper left central incisor was rotated 180° to accommodate the displaced canine. When engaged with a 0.019 × 0.025-inch stainless steel wire, the modified bracket approach effectively provided the desired labial root torque. The modified bracket selection approach successfully delivered the intended labial root torque.